The politics in and around governance in the New Partnership for Africa's Development - Roussel, Jean Thierry Kevin (Rhodes University, Faculty of Humanities, Department of Political and International Studies, 2006)
This study examines the prominence of the term governance and its use in multilateral organisations, in particular the New Partnership for African Development. It argues that the term governance is contentious and needs to be reviewed. This is in light of the elevation of governance as a requisite for development, which has come about through the development of NEPAD. This is primarily a study on the position of the state in multilateral regimes and how governance will affect the state and non-state actors. The politics in and around governance are therefore important in any assessment of African development as governance becomes a developmental necessity. The African Rennaisance and African Union have become 'beacons of hope' for Africa and these have been discussed here. We can see NEPAD as a historical development that fits into the African Renaissance. This has been a mechanism to ensure state survival and the states that drive NEPAD have played a significant role in providing legitimacy to Africa's calls for development. This thesis attempts to explain the shift in developmental policy in that NEPAD has seemingly become the first African development strategy that has the support of the West. Through this thesis, we will examine the role that the Post Washington consensus has played in getting this phase of African development started. What becomes significant here is the way in which governance has been accepted as the gauge for support in development. This study therefore aims to offer a means by which to analyse governance in multilateral organisations. As the term is contentious, three paradigms on governance will be provided in order to refine governance in such a way that it can be applied in analysis. This thesis shows that governance can be refined into corporatist, prebendal and conciliar forms. The form of governance that NEPAD will take has implications for the type of reconfiguration of the state brought about by governance.
Keywords: New Partnership for Africa's Development; Sustainable development -- Africa; Economic development -- Africa; Africa -- Foreign economic relations; Africa -- Economic conditions; Africa -- Politics and government